The urbanisation of Rome and Latium vetus from the Bronze Age to the archaic era - Fulminante, Francesca 1973- (Cambridge Univ. Press, 2014)
Offers an original and unprecedented analysis of urbanization and state formation in Rome and Latium vetus from the Bronze Age to the Archaic Era
Description based upon print version of record. - Rome during the Second Regal Period (End of the Recent Orientalizing Age, or Latial Phase IVB, and the Archaic Age, ca. End of
Cover; The Urbanisation of Rome and Latium Vetus; Title; Copyright; Dedication; Contents; Figures and Tables; Preface; Acknowledgements; Introduction; One Urbanisation and State Formation in Middle Tyrrhenian Italy: Historical Questions and Theoretical Models; 1.1. The Origin of the City in Middle Tyrrhenian Italy; 1.2. Approaches to Urbanisation and State Formation from a Comparative Perspective; Evolutionary Approaches; Multi-Trajectory (Anti-Evolutionary) Approaches; Recent Comparative Approaches: The Copenhagen Polis Centre Project
The Model of Social Evolution of the Roman School of Pre- and Proto-HistoryThe Socio-Ecological Model of Urbanisation Developed by John Bintliff; The Contribution of German Landscape Ideas and Territorial Behaviour Approaches to the Socio-Ecological Model of Urbanisation; The Contribution of Face-to-Face Social Organisation Theories to the Socio-Ecological Model of Urbanisation; The Socio-Ecological Model Applied to Urbanisation in Greece during the First Millennium BC; 1.3. Conclusions: Towards a Reconciliation; Two The Latin Landscape, Data and Methodology; 2.1. The Latin Landscape
Geography and MorphologyGeology; The Limits of Latium Vetus; The Nature of Settlement Development in Latium Vetus; 2.2. Data: Archaeological Research in Rome and Latium Vetus from the End of the Nineteenth to the Beginning of the Twenty-first; 2.3. Data Collected and Used in the Present Study; The Territorial Sample; The Regional Sample; Nature of the Data; Criteria for the Identification and Measurement of Settlements; 2.4. Methodology and Theoretical Issues; Settlement Patterns and Locational Models: Some Theoretical Issues
Geographical Information Systems, Determinism and Space: Current Theoretical Debate on the Use of GIS in Archaeology2.5. Conclusions; Three The City Level: Rome from a Small Bronze Age Village to the Great City of the Archaic Age; 3.1. Rome from the Bronze Age to the Archaic Age: Archaeological Evidence; Premise; Pre-Urban Rome (Bronze Age); Middle Bronze Age (Seventeenth to Fourteenth Century BC); Recent Bronze Age (Thirteenth Century BC); Final Bronze Age (Twelfth to Tenth Century BC); Proto-Urban Rome (Early Iron Age)
Keywords: Geschichte 1000 v. Chr.-500 v. Chr.; Geschichte 1000 v.Chr.-500 v.Chr.; Verstädterung; Latium; Rom; Hochschulschrift